Foreign Actors in Libya's Crisis - Karim Mezran (Pubblicazioni ISPI, 2017)
Since 2011 the Libyan crisis has moved from being a domestic dispute to assuming increasing importance at the international level. Today it represents a crucial issue affecting global security. The intervention of external actors in the Libyan crisis was mainly driven by a desire to direct the transition towards outcomes that would best meet their own political and economic interests. Accordingly, each external player tried to support one specific faction, favoring either the Parliament in Tobruk, upheld by Khalifa Haftar, or the Presidential Council headed by Fayez al-Serraj in Tripoli, the latter being legitimized by the UN as well as by local militias in both Misrata and Tripoli. This report analyzes the troublesome re-building of Libya with a focus on the specific role played by international actors (neighboring and Gulf countries, European nations, Russia and the US) which make it more of an international rather than a domestic issue.